Intervención farmacéutica para evaluar la eficacia de un tratamiento de tres días frente al de siete días con ciprofloxacino de 500 mg en infecciones sintomáticas no complicadas del tracto urinario en mujeres con diabetes mellitus tipo 2. hospital víctor lazarte echegaray - 2005 - Rodrigo Villanueva, Elda Maritza (2007)
The urinary infections are a frequently heath problem, their characteristics are the colonization and the invasion of pathogenic microorganisms. Diabetes mellitus may increase the predisposition of the patient to get this infections due to diminishing of the (polymorphous nucleares) function, the less antioxidant activity, the function of the T cellule and problems in the secretion of (citoquinas); because de lack of metabolic control in diabetic patients, in which the highest percentage is presented in woman. This research evaluates the efficiency of 3 days therapy with Ciprofloxacin in contrast of 7 day therapy in uncomplicated but symptomatic urinary infections in woman with diabetes mellitus type 2. The patient risk’s have been evaluated by clinical and laboratory control. The percents have been admitted in the infectology and internal medicine offices in Victor Lazarte Hospital of Trujillo from the ages between 50 and 70. They are included in two groups of 190 patients. In the evaluation one determined that there is no statistical difference in relation to the efficiency of the antimicrobial treatment of 3 days versus 7 days with Ciprofloxacin. Nevertheless the patients who received therapy of 3 ó 7 days with ciprofloxacin 500 mg. presented the same risk of reinfection or recurrence of the IU and the patients with high levels of glucose present major risk of contracting IU infection of the urinary tract.